The Battles of Al-Taf & Maldon Between History & Literature (Journal of the College of Languages (JCL), 2009)
It was Aristotle who first drew attention to the superior quality of literature to the other factual fields of knowledge. Contradicting his predecessor Plato on the issue of „truth,‟ Aristotle believed that „poetry is more philosophical and deserves more serious attention than history: for while poetry concerns itself with universal truths, history considers only particular facts.‟ (1) The critical attention to the disparity between the literary truth and the historical truth grew up throughout ages to flourish in the Renaissance and after with a bunch of distinctive views on this subject. Sir Philip Sidney (1554-1586), for example, found that literature does not offer a literal description of reality but rather a heightened version of it. Reality of nature, to him, is „brazen‟ where as poets deliver only a „golden‟ one. For this reason, poetry, unlike history which is too tied to „particular facts,‟ is ideal in its golden fables „to win the mind from wickedness to virtue.‟(2) It is, in other words, a matter of ethical value represented by the literary potency of the moral lesson.The development in understanding the poetic truth has